2020
DOI: 10.1002/jhbp.821
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐chain amino acid to tyrosine ratio is an essential pre‐treatment factor for maintaining sufficient treatment intensity of lenvatinib in patients with hepatocellular carcinoma

Abstract: More than 500 000 cases of hepatocellular carcinoma (HCC) are diagnosed every year; and HCC is one of the leading causes of cancer-related deaths worldwide. 1 For patients with early-stage HCC, either surgical resection or ablation are offered. 2 However, the treatment options for unresectable advanced-stage HCC are limited, and the prognosis is still poor because of the high potential for intra-and extra-hepatic recurrence. An oral tyrosine kinase inhibitor sorafenib was approved in 2007 as the first

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this study, the BTR before the start of treatment was extracted as an independent factor for treatment duration. This is similar to the report by Eso et al 11 The BTR is an index of abnormal protein/amino acid metabolism in chronic liver disease as well as the Fisher ratio (branched chain amino acids/aromatic amino acids). In cases of liver cirrhosis, branched-chain amino acids are used as an energy source and for ammonia metabolism; thus, they decrease in the blood.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the BTR before the start of treatment was extracted as an independent factor for treatment duration. This is similar to the report by Eso et al 11 The BTR is an index of abnormal protein/amino acid metabolism in chronic liver disease as well as the Fisher ratio (branched chain amino acids/aromatic amino acids). In cases of liver cirrhosis, branched-chain amino acids are used as an energy source and for ammonia metabolism; thus, they decrease in the blood.…”
Section: Discussionsupporting
confidence: 91%
“…Takahashi et al previously reported that patients with RDI ≥75% during the initial 8 weeks of lenvatinib treatment experienced a higher response rate and longer PFS than those with RDI <75% 17 . We have also reported that the dose intensity of lenvatinib during the first 60 days of treatment strongly correlated with ORR and was a significant factor that contributed to prolonged PFS 5,6 . In other words, if patients do not tolerate lenvatinib therapy, they are consequently not expected to achieve sufficient dose intensity and therefore unlikely to benefit from it.…”
Section: Discussionmentioning
confidence: 60%
“…3 Several studies have demonstrated that lenvatinib has comparable therapeutic efficacy in real-world clinical practice, as observed in the REFLECT trial. [4][5][6] Importantly, these data support a strong correlation between the relative dose intensity (RDI), which is defined as administered dose in a systemic therapy divided by the planned dose, and therapeutic efficacy of lenvatinib. However, sufficient RDI of lenvatinib is not achieved in a significant number of treated patients due to associated adverse events (AEs).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The BTR was a prognostic indicator for early HCC and a predictive indicator for intrahepatic recurrence and survival based on 50 HCC patients at stage I/II. 36 Yuji et al 37 found that the BTR was an essential pretreatment indicator on maintaining the efficacy of lenvatinib in patients with HCC. Hiraoka et al 38 concluded a low BTR (≤4.4) may be an available prognostic indicator in early HCC patients.…”
Section: Discussionmentioning
confidence: 99%